Using a frequency vibration approach, examine the impact of screw rotor clearance on the screw housing in an 11kW compressor - Tri Haryono; Deni Arif Rahman deni; Subekti Subekti; Abdul Hamid (JTTM : Jurnal Terapan Teknik Mesin, 2024)
A screw compressor is one of the industrial machines needed for productivity and use in today's production. Industrial machines generally use pneumatic systems with the help of compressed air supplied by a compressor machine. The compressor working system must receive very special attention. Maintenance and prevention of damage to air screw compressor machines is very necessary, especially maintenance and prevention of damage to rotary screw air compressors. Problems that often occur with the shaft will result in reduced air supply flow or unstable air pressure resulting in disruption of the production line. The aim of this research was to discuss the vibration values produced against the rotor clearance from the ideal output on male and female screw compressor rotors using the frequency analysis method, taking the vibration values at the screw compressor housing point using an Accelerometer sensor and a Fast Fourier Transform (FFT) tool. The analyzer rotates at 1500 rpm in the X, Y and Z axes at each predetermined point. Research shows that the clearance is set at 0.03, 0.05 and 0.08. In this research, the high frequency sample values of 1x 25 Hz, 2x 50 Hz, and 3x 75 Hz often appear in each vibration data of 0.03 and 0.05, at the vibration frequency range value of 0.08 none appear. This shows the results that the ideal rotor clearance value is at a distance of 0.08 because there is no frequency graph of 1x, 2x, and 3x rpm at each point and axis on the end housing of the screw rotor compressor